Optimization on the complementation procedure towards efficient implementation of the index generation function - Borowik, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
In the era of big data, solutions are desired that would be capable of efficient data reduction. This paper presents a summary of research on an algorithm for complementation of a Boolean function which is fundamental for logic synthesis and data mining. Successively, the existing problems and their proposed solutions are examined, including the analysis of current implementations of the algorithm. Then, methods to speed up the computation process and efficient parallel implementation of the algorithm are shown; they include optimization of data representation, recursive decomposition, merging, and removal of redundant data.
Keywords: data reduction; feature selection; indiscernibility matrix; logic synthesis; index generation function